Black Images in Contemporary Slavery-Themed Novel Written by Whites American: Reflecting the Persistence of White Supremacy - Rasiah Rasiah; La Bilu Bilu (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2021)
This study investigates images of black (and white) characters in contemporary American slavery-themed novel written by white authors, focusing on two novels, Property (2003) and Rhett Butler’s People (2007). The theoretical hegemony of Gramsci is utilized to suggest that if the slavery-themed novel is still rewritten in the era of twenty-first century, it should have a new insight about racism and should be also understood. Three points that revealed by this article dealing with hegemonic discourse on both novels; the representation of black beauty, black behavior, and the relation of black-white attested that the white supremacy is still sustained in the USA. The change of the story composition is there, but the racist ideology kept existed in the subtle way.